Calculation of water balance China Lake (between 2008-2014) - Zh.R. Shakirzanova; Y.S. Medvedeva; M.D. Yaneva (Український гідрометеорологічний журнал, 2015)
Introduction. The main characteristic of  hydrometeorological mode of China Lake, is the water balance of inland waters, defined process flow and water flow. Based on the water balance is determined by water exchange, physical and chemical processes in reservoirs and estimated effects of measures aimed at possible economic use of water resources.